PENDIDIKAN TAUHID TERHADAP MOTIVASI HIDUP DALAM PERSPEKTIF AL-QURAN - Iskandar, Topan (Universitas Al-Amien Prenduan, 2022)
Tasawwuf morality is a study of knowledge in knowing the Creator or God. This paper will describe and analyse how to develop morality in the study of Sufism by a Muslim community organization located in Batu Bara Regency. The purpose of this research is to form young morals and have a strong belief in the Creator in humans so that they become perfect human beings through the study of Sufism. This study uses the internalization of religious values through dzikrullah (dhikr darajah and khasanah) with the takhalli, tahalli and tajalli methods which are included in a qualitative descriptive study. The results obtained from this study are that the Development of Sufism is very important to be known and studied by every special human being with Muslim status in the Batu Bara district community. Through the development of Sufism Akhlak, it will also bring a person who has good character so that he can easily live life from the development of the times and be able to adapt easily.Â